The Role of the Indonesian Ulema Council as the Giver of Fatwa - Farid Wajdi (International Journal of Economic, Technology and Social Sciences (Injects), 2021)
The provisions of Article 48 number 10 paragraph (2) of the Copyright Law affirm,"The determination of the page of the Product as referred to in paragraph (1) is issued by MUI in the form of a Halal Product Determination Decree." Theissue of the Copyright Law does not change the authority of MUI in the determination of product page. Article 33 Undang-Undang Halal Product Guarantee stipulates that the determination of product idolatry is carried out by MUI through the implementation of the MUI Halal Fatwa Session. Undang-U's legal mandate  for Halal Product Guarantee and Work Copyright Law to MUI as the authority holder of halal determination of products is based on philosophical, historical and sociological factors. The research method used in this research is normative juridical. The results showed that the  position of the MUI Fatwa has moral power for groups that have aspirations to implement it, but cannot be used as a tool of force for other groups who disagree over it. Because the MUI Fatwa is not a positive law of the state that has coercive power. Halal  fatwa standards have an important role to play in order to provide protection and comfort for Muslim consumers.